Variasi Pemberian Pupuk Organik Kotoran Sapi dan Ayam terhadap Tanaman Buncis sebagai Upaya Meningkatkan Produktivitas Usahatani Buncis - Jacky Muchtar (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2020)
One of the important things in bean farming is the use of superior seeds supported by the use of organic fertilizers with the right type and dosage so that the productivity of beans will be optimal. This study aims to study the interaction between types and doses of cow manure and chicken manure on the growth and yield of bean pods and to find out the optimum dose of manure fertilizer which has the most optimum effect on the production of bean varieties of Balitsa-2 (Phaseolus vulgaris). The study was carried out at the Lembang Vegetable Research Institute (BALITSA) by using a design of two different average factorial patterns with two factors and three replications and quadratic regression analysis with response surface models. The results of the study on each component of growth and yield of pod production showed significant differences from each treatment at d3 (15 tons / ha) and there was an interaction between the treatment and the dose given to the yield. The treatment of p1 (cow manure) and p2 (chicken manure) by dosing d3 (15 tons / ha) gave the most optimum results of fresh pods and was not significantly different, respectively 10,549 tons / ha and 10.726 tons / ha based on quadratic regression analysis. Thus, it is expected that bean farmers use superior bean seeds and fertilize organically both using chicken manure or cow manure at a dose of 15 tons / ha in order to obtain optimal bean production.